RECKONING THE COACHING STYLES OF CAGAYAN STATE UNIVERSITY COACHES - Tabao, Mark John (International Journal of Arts, Sciences and Education, 2022)
Abstract For an athlete to achieve success in their chosen sport, the capacity to maintain their motivation is absolutely necessary. One of the many external factors that can have an effect on an athlete throughout their entire career in their sport is the relationship that exists between them and their coach. However, of all of these external factors, the relationship between a coach and an athlete is one of the most important for both motivation and performance. The primary objective of this research is to identify and explain the various coaching styles utilized by university coaches that are currently employed by Cagayan State University. In the design of this study, a descriptive-correlational approach was adopted as the method of inquiry. The objective of the descriptive design is to provide not only a profile of the coaches but also an examination of the coaching style that each of them use. The evaluation is based on five subscales, which include the following: a focus on training and teaching; a democratic style; an autocratic style; a focus on social support; and a focus on feedback and reward. Each subscale is weighted equally in the overall evaluation. The majority of the coaches believe that the primary focus of coaching should be on teaching the athletes and providing instructions on what the sport is all about, as well as how to play the sport and excel at it. This view is supported by the fact that this should be the primary focus of coaching. This might be interpreted as the coaches acknowledging the fact that the athletes know themselves better than anybody else does.